Significant transcriptomic changes are associated with the inhibitory effects of 5-aza-2-deoxycytidine during adipogenic differentiation of MG-63 cells - Amir Ali Khan (Elsevier, 2021)
Our previous study revealed that the treatment of 5-aza-2-deoxycytidine (5-aza) inhibited while treatment of suberoylanilide hydroxamic acid (SAHA) enhanced the adipogenic differentiation of MG-63 cells. In this study, we examined the transcriptomic profiles of the derived adipocyte-like cells from MG-63 cells in the presence of 5-aza (Treatment 1) and SAHA (Treatment 2). Genome wide expression analysis showed high within sample variability for the adipocytes derived with 5-aza versus vehicle. Additionally, the expression profile of 5-aza derived cells was separated from the other sample groups. Differential analysis on the pairwise comparison of 5-aza versus control and SAHA versus 5-aza identified 1290 and 1086 differentially expressed (DE) genes, respectively. Furthermore, some overlap was observed between the up and down-regulated DE genes of 5-aza versus control and SAHA versus control (jaccard score 0.3) as well as between the differentially regulated genes of 5-aza versus control and 5-aza versus SAHA (jaccard score 0.29). A total of 73 transcription factors (TFs) were differentially expressed across all the pair wise comparisons with some overlap between the under and over expressed TFs of 5-aza versus control and 5-aza versus SAHA (jaccard score 0.29). Unsupervised clustering of TFs showed that the samples within the group are consistent in expression and the samples cluster in accordance with the group.Several GO terms related to enhanced adipogenesis such as neutral lipid biosynthetic process, lipid metabolic processes, cellular amide metabolic processes and cellular carbohydrate metabolic processes were enriched in the down regulated genes of 5-aza derived adipocytes versus control, indicating 5-aza inhibit the adipogenic differentiation of MG-63 cells. GSEA analysis on selected gene sets of MAPK and PI3K signaling pathway in MSigDB identified the pathways were up-regulated in 5-aza versus control. This study revealed that inhibition of MG-63 adipogenesis due to 5-aza treatment is associated with large transcriptomics changes and further research is needed to unravel the roles of these genes in the adipogenesis.